PENGEMBANGAN MEDIA TALOKA (TALI LOMPAT ANGKA) UNTUK MENINGKATKAN KEMAMPUAN MENGENAL ANGKA PADA ANAK USIA DINI - INDARIA HARIYANI (Universitas Muhammadiyah Metro, 2020)
The recognition of numbers in children is not only about knowing the symbol of a number, but children are able to know the meaning or value of a number. The purpose of this research is to develop TALOKA media which is considered interesting to solve the existing problems, especially in the ability to recognize numbers in early childhood. The development method used in this study is a modification of the 4D Thiagarajan development model. The resulting data will be analyzed using qualitative descriptive analysis, quantitative descriptive analysis and t test. The results showed that TALOKA media can improve the ability to recognize numbers in early childhood. From the results of data analysis obtained a significance value of 0.000 <0.005, then H0 is rejected. Thus it can be said that there is a difference in the average before and after treatment and the average score of the treatment before and after treatment in the learning process using TALOKA Media that has been developed. The difference in the mean value of the experimental group and the control group proves that using the TALOKA Media that has been developed can improve the ability to recognize numbers in early childhood.